Vulnerability to climate change among the livestock rearers of eastern coastal region of India: A household level assessment - MAITI, SANJIT; JHA, SUJEET KUMAR; GARAI, SANCHITA; NAG, ARINDAM; CHAKRAVARTY, R; KADIAN, K S; CHANDEL, B S; DATTA, K K; UPADHAYAY, R C (The Indian Journal of Animal Sciences, 2014)
The impact of global climatic change on agriculture as well as livestock has recently become a subject of increasing importance particularly in coastal ecosystem. The present study was designed to assess climate induced vulnerability at household level among the livestock rearers of eastern coastal region. Total 480 livestock rearers were randomly selected from the 4 coastal districts of 2 eastern coastal states of India as respondents. An exclusively “Social Vulnerability to Climate Change” index was developed by considering 40 indicators. The study revealed that average index score of vulnerability of livestock rearers of each studied districts as well as coastal states were negative with overall mean value -15.503±0.214. It was also found that livestock rearers of South 24 Parganas district were comparatively most vulnerable followed by Bhadrak, Ganjam, and Purba Medinipur districts. In overall, 41.667% of the livestock rearers were in medium vulnerability category followed by 35% and 23.333% in lower and higher vulnerability category, respectively.